2018
DOI: 10.5812/jjcdc.79182
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Spiritual Intelligence and Emotional Intelligence in Patients with Type 2 Diabetes

Abstract: Background: Diabetes mellitus is a chronic, destructive metabolic disease. One of the factors that can affect the mental and physical health of diabetic patients is spiritual intelligence and emotional intelligence. Objectives: This study aimed to investigate the relationship between spiritual intelligence and emotional intelligence in patients with type 2 diabetes. Methods: This descriptive-correlational study was performed on 100 patients with type 2 diabetes who referred to the Kermanshah Diabetes Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…As displayed in Table 1, emotional and self-management sub-themes were deemed crucial (65.1%), while leisure and outdoor activities accounted for less than 10% of the recommendations. Emotional intelligence and spiritual development are essential for achieving life's ultimate goal; thus, low emotional intelligence can lead to negative emotions and increase the risk of several illnesses (Jamalnia et al, 2018). As such, students were advised to practice mindfulness, breathing exercises, and journaling to regulate their emotions and reduce stress and anxiety.…”
Section: Self-carementioning
confidence: 99%
“…As displayed in Table 1, emotional and self-management sub-themes were deemed crucial (65.1%), while leisure and outdoor activities accounted for less than 10% of the recommendations. Emotional intelligence and spiritual development are essential for achieving life's ultimate goal; thus, low emotional intelligence can lead to negative emotions and increase the risk of several illnesses (Jamalnia et al, 2018). As such, students were advised to practice mindfulness, breathing exercises, and journaling to regulate their emotions and reduce stress and anxiety.…”
Section: Self-carementioning
confidence: 99%
“…Emons defines the emergence of spiritual intelligence as the use of spiritual resources and capacities in real‐world contexts and situations. In other words, people employ spiritual intelligence when they desire to harness spiritual resources and talents to make crucial decisions, consider existential issues, or attempt to address everyday problems 12 . A study showed a correlation between emotional and spiritual intelligence 13 …”
Section: Introductionmentioning
confidence: 99%
“…Wong and Law's emotional intelligence questionnaire (2002) consists of 16 items and includes four dimensions: evaluation and expression (1-4); emotional understanding and analysis(5)(6)(7)(8); use of emotions to facilitate thought(9)(10)(11)(12); and emotional regulation(13- 16). A 5-point Likert scale was assigned scores (1 = completely opposed, 5 = completely agree).…”
mentioning
confidence: 99%
See 1 more Smart Citation